Find the Multiplication of the following…..
I) (x + 8) (x – 10)
II) (3 – 2x) (3 + 2x)
Answers
Answered by
1
Step-by-step explanation:
I) (x + 8) (x – 10)
= x^2 + 8x -10x -80
x^2 -2x -80
II) (3 – 2x) (3 + 2x)
= 9 -6x +6x-4x^2
9-4x^2
Answered by
0
Answer:
1) = x (x) + 8 (x) - x (10) - 8 (10)
= x² + 8x - 10x - 80
= x² - 2x - 80
2) By identity of [(a² - b²) = (a+b) (a-b)],
3² - (2x)²
= 9 - 4x²
Similar questions
Math,
2 months ago
Math,
2 months ago
Math,
2 months ago
Math,
11 months ago
Social Sciences,
11 months ago